Artificial Intelligence and Journalism Education in Higher Education: Digital Transformation in Undergraduate and Graduate Curricula in Türkiye - Hatice Babacan; Emel Arık; Yasemin Bilişli; Hakkı Akgün; Yasin Özkara (Journalism and Media)
This study investigates the integration of artificial intelligence (AI) into undergraduate and graduate curricula in journalism and new media programs in Türkiye, offering a systematic analysis of course structures and content. Utilizing a qualitative research approach, this study combines document analysis and thematic content analysis to examine course catalogs, syllabi, and institutional reports from 72 universities. The findings reveal that AI education in these programs is predominantly theoretical, with courses emphasizing AI ethics, media algorithms, and the impact of automation on news production. Practical applications, such as data journalism and AI-assisted content creation are comparatively scarce. This study highlights the uneven distribution of AI-related courses across institutions, illustrating significant disparities in curriculum depth and focus. While some universities have embraced a more comprehensive AI framework, others offer minimal exposure to AI-related competencies. By systematically mapping AI course distribution across institutions, this study provides empirical insights into the gaps and disparities in AI education, offering recommendations for a curriculum compatible with digital transformation.